Oral cancer screening in private dental practices in a developing country: opportunities and challenges. Issue 2 (2nd November 2016) - Saleh, Amyza; Kong, Yink Heay; Haron, Nabihah; Aripin, Siti Fatimah; Vadiveloo, Malliga; Hussaini, Haizal; Zain, Rosnah Binti; Cheong, Sok Ching
Abstract: Objectives: Private dental practitioners constitute approximately 40% of all registered dentists in Malaysia, and this group affords an avenue for prevention and early detection of oral cancer. However, such activities are still limited. This study investigated the feasibility of incorporating opportunistic screening of oral cancer in the private dental setting. Methods: Dentists were recruited through two main dental associations in Malaysia and attended a 1‐day training session on recognizing abnormalities within the oral cavity. Following the training, the dentists conducted screening and provided risk habits cessation advice at their respective clinics for 6 months. The impact of the program was evaluated by determining the number of patients who were screened and/or provided with risk habits cessation advice. Results: Twenty‐six dentists took part in the program and conducted opportunistic screening on a total of 2603 individuals. On average, they screened about 23.0% of their patients and 5.1% were given risk habits cessation advice. Notably, dentists who had lower patient load were more likely to conduct opportunistic screening. Conclusions: While the participating private dentists state that they have a role in performing opportunistic screening and providing risk habits cessation advice, these activities are still not a priority area in the private clinics, strongly suggesting that strategies to motivate dentists in this setting are urgently needed.